Pengaruh Pupuk Organik Cair (POC) Urine Kelinci Terhadap Pertumbuhan dan Hasil Tiga Varietas Tanaman Bawang Merah (Allium ascalonicum L.) - Ramadhani, Fajariska Desi; Augustien K., Nora; Sutini, Sutini (BIOEDUSCIENCE, 2025)
Background: Shallots (Allium ascalonicum L.) are a commodity that contributes significantly to the country's foreign exchange, holding high economic value. Rabbit urine, when processed into liquid organic fertilizer, provides plants with the macro and micro nutrients they need. This study aims to investigate the interaction between liquid organic fertilizer concentrations derived from rabbit urine and three varieties on the growth and yield of shallots. Method: The method chosen for this study was a Completely Randomized Design (CRD) consisting of two treatment factors: three varieties of shallots (Bima Brebes, Bauji, and Tajuk) and five levels of rabbit urine LOF concentration (0, 100, 250, 400, and 550 ml/L). and obtained 15 combinations (V1, V2, V3 and K1, K2, K3, K4, K5). Results: Significant interaction occurred in the number of leaves aged 7–14 HST. The Bima variety showed the best vegetative growth, while the Tajuk variety produced the highest number of bulbs. A concentration of 550 ml/l gave the highest results in plant length, number of leaves, and wet and dry weight of the stover. Conclusion: Rabbit urine LOF concentration of 550 ml/l is effective in increasing the growth and yield of shallots, especially in the Bima variety.